KETERKAITAN JALINAN INTERPERSONAL DAN TEMPAT KERJA TERHADAP KEPUASAN KERJA KARYAWAN MA’HAD MUHAMMADIYAH DAARUL ULUM MAJENANG CILACAP - Mudiono, Mudiono; Sya’bana, Ali; Sutanto, Aftoni; Asakdiyah, Salamatun (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2019)
This paper tries to reveal the relationship of interpersonal relation and work environment toward job satisfaction of employees in ma'had Muhammadiyah Daarul Ulum Majenang Cilacap. This research was carried out on all existing active employee, which are 50 people. This study utilizes the instrument test and hypothesis test through SPSS 16.0 for Windows. The findings show that based on the t test, the value of tcount is 3.147> t table 1.299 and the significant value is 0.003 <0.05. Therefore, it can be claimed that partially interpersonal relations (X1) significantly influence employee job satisfaction. While the work environment variable tcount 10.390> ttable 1.299 and a significant value of 0.000 <0.05. Consequently, it can be claimed that partially work environment consist of a substantial influence on employee job satisfaction. Based on the F test, Fcount 194.06> Ftable 3.19. Hence, it proved that interpersonal relations and work environment jointly influence job contentment. Furthermore, the analysis of determination shows a significant contribution from interpersonal relations and work environment on employee job contentment, as obtained R square (R2) of 0.892. Thus, 89.2% of employee job satisfaction is influenced by interpersonal relations and work environment, while the remaining 10.8% is affected by different variables which is not executed in this study.